Digitale Gesundheitskommunikation Zwischen Meinungsbildung und Manipulation - Pundt, Johanne (Themenband, 2018)
With the sharp rise in information and communication systems in the health sector, the importance of digital health communication is increasing: patient care should be individualized, personal responsibility strengthened and the patient better integrated into the care processes. But digitization is also associated with many open questions: Is the vision of optimized health an opportunity or a nightmare for the transparent person? Do the numerous digital prevention offers increase health literacy or are they manipulation in the guise of education? Since a successful digital change process is characterized by sensitivity and a sense of responsibility on all sides, ethical, quality-related, data protection and target group-specific aspects of digital health communication are discussed from different perspectives in this book. The textbook offers a forward-looking insight into the topic and shows how digitization can be used profitably for all parties involved and is therefore just as suitable for practitioners as it is for students and lecturers at universities. With prefaces by Prof. Dr. Heinz Lohmann and Prof. Dr. Horst Opaschowski!